Monitoring patient satisfaction with university dental services under two fee-paying systems - Chu CH, Yeung CYYJ, Lo ECM (Blackwell Synergy, 2001)
The aim of this survey was to study patients’ satisfaction with the dental service of a university in Hong Kong under a recently introduced itembased fee-paying system and reasons for non-attendance at the clinic; and to compare results of the present survey with that of a similar survey of the same dental service under a time-based fee-paying system in 1996.